Enteral Feeding in the Surgical Patient. The use of B. P.C.: Prospective Study - Bertullo, Hugo; Balboa, Oscar; Silva, Julia; Leivas, Julieta (Cirugía del Uruguay, 1981)
A comparative and prospective experience of 41 surgical patients, of whom 32 had a localized or generalized neoplasia, is undertaken to compare the benefit of enteral feeding with two proteic suplements.